WxMaxima computer software as an aid to the study of calculus by students with different learning approaches - Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani; Abu Bakar, Kamariah; Wong, Su Luan (Elsevier, 2012)
This study examined the effectiveness of teaching and learning calculus with the aid of the WxMaxima computer programme, as compared with the traditional method. In a quasi-experimental study, two classes of Malaysian secondary school Form Four students were randomly assigned to the control group (30 students) and the WxMaxima group (32 students). A Study Process Questionnaire (SPQ) was initially used to identify students with deep and surface approaches to learning. The findings indicated that students who were taught using the WxMaxima software performed significantly better than those in the traditional learning group. Further analysis showed that students with the deep learning approach in the experimental group achieved significantly higher post-test scores compared with students in the traditional learning group. However, there was no significant difference between the scores of the control and experimental groups who adopted the surface learning approach. This study implies that the use of WxMaxima could help students learn calculus more effectively, this being especially true among students who use the deep study approach.